Scabies in children - Kecelj-Leskovec, Nada (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1998)
Scabies is a persistent, contagious pruritic skin eruption caused by cutaneousinfestation with the mite Sarcoptes scabiei. Usually parents and children are infected at the same time, because scabies infestations are transmitted mostly by direct contact. The peak incidence of scabies in children, which have been treated at the University Department of Dermatology in Ljubljana from 1990 to 1997, was observed from 1993 to 1995 with approximately 163 cases per year. History, clinical feactures, and laboratory examinations are important for diagnosis. Clinical features are different in infants and in children, because infant's skin is still immature. The lesions in infants are of a more exudative character. They can be detected almost everywhere on the skin, important sites are soles, palms, face and scalp. Variants of scabies, differential diagnosis and treatment of scabies in children are reviewed. We should consider the diagnosis of scabies whenever the patient has persistent papulovesicular lesions, the itch worsening at night, and there are additional cases involving othe persons at home.
Keywords: Child; dermatologija; Diagnosis; Diagnosis, differential; Drug therapy; epidemiologija; Epidemiology; infekcijske bolezni; kožne bolezni; otroci; Scabies; skabies